Preventive Education Model Based on Multiculturalism and Local Wisdom for Reducing the Impact of Drugs among School Students in Madura - Achmad Muhlis; Moch. Cholid Wardi; Sri Rizqi Wahyuningrum; Moh. Wardi; Ani Cahyadi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to investigate the implementation of a preventive education model based on multiculturalism and local wisdom for dealing with the effects of drugs among school students in Madura. This research uses a qualitative approach with a case study method. The research participants were students from two schools in Madura who had been exposed to or were at risk of being exposed to drugs. Data was collected through interviews and analyzed using the thematic analysis technique. The research results showed that forms of drug control among students in Madura are carried out in 3 ways, namely medical rehabilitation is carried out using screening results data which is used as a reference for assessment and followed up by administering doses of drugs in the form of methadone pills and buprenorphine; non-medical rehabilitation is carried out using a psychological approach which includes counselling services, community therapy and spiritual therapy with talqin al dzikr through the qadiqah qadir naqsyabandiyah; and further rehabilitation is carried out using the Disease Model of Addiction through the development of vocational-based skills and activity management. The development of a model for overcoming the effects of drugs among students in Madura based on multiculturalism and Madurese local wisdom consists of three categories, namely: spiritual collaboration with certain amaliyah, spirituality collaboration with local wisdom of the koteka'an type, and collaboration of various types of local wisdom in the form of koteka'an.